Performance and preference of Bemisia tabaci on cucumbers: Understanding the recent outbreaks of Mediterranean cryptic species in Brazil - Gorayeb, Eduardo Silva [UNESP]; Maranho Watanabe, Luís Fernando [UNESP]; Barbi Pereira, Yago Alexandre [UNESP]; Dovigo, Leonardo Hipólito [UNESP]; Bello, Vinicius Henrique [UNESP]; Morcilo de Souza, Isabela [UNESP]; Dourado Cruciol, Giovana Carolina [UNESP]; Vicentin, Eduardo [UNESP]; Pereira Sartori, Maria Márcia [UNESP]; Krause-Sakate, Renate [UNESP] (Elsevier, 2021)
Currently, in Brazil, part of the cucumber production is cultivated in greenhouses, in rotation with bell pepper and tomato. However, this kind of cultivation seems to be contributing to heavy infestations of Bemisia tabaci Mediterranean cryptic species (MED) in cucumbers, which is indeed related to the recent detection of tomato chlorosis virus (ToCV) in this crop. Thus, the present study investigated the settling preference of B. tabaci Middle east Asia-Minor 1 (MEAM1) and MED cryptic species for cucumber, bell pepper, and tomato plants cultivated in the same area. In addition, the settling preference and biological performance of MEAM1 and MED on representative cucumber commercial cultivars were also compared. Cucumber was the most preferred host when compared with tomato and bell pepper for both whiteflies, which were also capable of establishing and ovipositioning in all cucumber cultivars tested. The Mediterranean species showed better adaptability than MEAM1 in almost all cucumber cultivars tested, by showing a better capacity of survival and resulting in a more significant number of adults. When evaluating cultivars, ‘Aodai’ stood out for presenting high MEAM1 nymph mortality, showing that it may be a good option to be implemented in areas with the absence of MED. In contrast, no cultivars were potentially satisfactory for use in the management of MED, reinforcing the need to develop specific management strategies directed for this cryptic whitefly species.
Keywords: Biological performance; Cucumis sativus; Fitness; Settling-preference; Whitefly behaviour